Integrated Antihypertensive and Statin Treatment Protocols for Cardiovascular Disease Prevention in Low- and Middle-Income Countries - Andrew E. Moran; Obehi Aimiosior; Reena Gupta; Anupam Pathni; Swagata Kumar Sahoo; Girma Dessie; Kufor Osi; Xiulei Zhang; Bolanle Banigbe; Renu Garg; Thomas R. Frieden (Global Heart)
In low- and middle-income countries where the majority of preventable cardiovascular disease deaths occur, less than 10% of eligible patients receive statins for primary cardiovascular disease prevention. Since 2017, the Global Hearts initiative has implemented simple World Health Organization (WHO) HEARTS hypertension and diabetes treatment protocols. In this editorial, we propose an approach of integrating statin treatment into existing HEARTS hypertension and diabetes protocols as a way of expanding statin coverage in low-and middle-income countries.